2012
DOI: 10.1021/jp209157y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Interactions between Dipolar Membranes

Abstract: It is well-known that phospholipids in aqueous environment self-assemble into lamellar structures with a repeat distance governed by the interactions between them. Yet, the understanding of these interactions is incomplete. In this paper, we study the effect of temperature on the interlamellar interactions between dipolar membranes. Using solution small-angle X-ray scattering (SAXS), we measured the repeat distance between 1,2-dilauroyl-sn-glycero-3-phosphocholine (DLPC) bilayers at different temperatures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 35 publications
3
30
0
1
Order By: Relevance
“…4 , red square symbols). Previous studies had shown such behavior, explained by a decrease in the membrane thickness ( ) with increasing temperature ( 59 ). The different trends can be explained by the formation of a mixed phase at modified lipid composition, and a single lamellar phase at the native lipid composition.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…4 , red square symbols). Previous studies had shown such behavior, explained by a decrease in the membrane thickness ( ) with increasing temperature ( 59 ). The different trends can be explained by the formation of a mixed phase at modified lipid composition, and a single lamellar phase at the native lipid composition.…”
Section: Resultsmentioning
confidence: 86%
“…For example, at elevated temperature, the lamellar to hexagonal phase transition has been demonstrated for single and binary lipids mixtures ( 24 , 56 58 ). The origin of this thermotropic phase transition is the added mobility of the hydrocarbon chains at elevated temperatures, leading to larger spontaneous curvature ( 23 , 59 ). The contribution of hydrocarbon chains’ entropy to the free energy increases with temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To apply osmotic stress to the flagellar filaments and induce bundle formation, we used polyethylene glycol (PEG) of molecular mass 20 kDa (purchased from Sigma-Aldrich (St. Louis, MO) and used as received). Osmotic stress samples were prepared by mixing PEG and flagellar filament solutions, as described elsewhere (16)(17)(18)(19). The osmotic pressure, P, of each polymer solution was measured using a vapor pressure osmometer (Vapro 5520, Wescor, Pittsburgh, PA) and verified against the well-established (20) expression log p ¼ a þ b  ðwt%Þ c , where a ¼ 1:57, b ¼ 2:75, and c ¼ 0:21.…”
Section: Methodsmentioning
confidence: 99%
“…En [43] se mostró un modelo lineal y otro cuadrático para determinar la conductividad térmica del acero en estado líquido, pastoso y sólido en el molde. En la zona de conducción en el acero sólido, la conductividad térmica del acero sólido se ha asumido constante [48], [49] o lineal con la temperatura [50], sin embargo, no debe descuidarse su influencia, porque habrá una mayor transferencia de calor donde la capa de acero es más delgada (en el menisco) y disminuirá con la longitud del molde. Además, por tratarse de una aleación, se formará una zona pastosa cuya conductividad térmica dependerá de las fases [11], [12], [16], y esto afecta la transferencia de calor.…”
Section: = ( )unclassified